Perdas quali-quantitativas na colheita mecanizada de sementes de amendoim (Arachis hypogaea L.) - Barrozo, Leandra Matos [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The experiment was carried out in the experimental FARM and in the Analysis and in the Phytopatology Laboratories belonging to College of Agriculture, São Paulo State University, Campus of Jaboticabal. The objective of this research was to quantify the losses of peanut crop harvesting and, also the qualitative, it was used a cultivar Runner IAC 886, and was analyzed the effect of the groundnut digger and the harvesting combine speeds. Were used two groundnut digger speeds (4.3 and 5.0 km h-1) and three harvesting combine speeds (3.5; 4.6 and 6.2 km h-1). In the digging process were evaluated the visible losses (PVA), the invisible losses (PIA), total losses groundnut digger (PTA), total visible losses (PVT), total losses in the crop (PTC), design of piles, distribution of straws and the real production. To the physiological quality were used the germination percentage (in sand and paper), first germination count, speed of emergence, seedling dry matter, accelerated aging, electrical conductivity, seedling emergence at field conditions and tetrazolium. For the statistical analysis it was used a completely randomized design consisting of two groundnut digger speed. In the combined harvesting was used a randomized block design in a split plot scheme. The plots were composed by two digger speeds and the split split plot by three combine harvesting speeds. The physiological seed quality were analized by the Shapiro-Will test and after were submitted to the analys of variance together with the sanity data, and the means compared by the Tukey test at 5% level of probability. The maximum and minimum speeds didn't influence in the qualitatife and quantitative losses of the peanut seeds.

O experimento foi conduzido na área da Fazenda de Ensino, Pesquisa e Produção e nos Laboratórios de Análises de Sementes e Fitopatologia da Faculdade de Ciências Agrárias e Veterinárias – FCAV/UNESP, Câmpus de Jaboticabal. O objetivo foi verificar as perdas quantitativas e qualitativas da cultura do amendoim, cultivar Runner IAC 886, em função das velocidades de arranquio e recolhimento. Foram utilizadas duas velocidades de arranquio (4,3 e 5,0 km h-1) e três de recolhimento (3,5; 4,6 e 6,2 km h-1). Foram avaliadas as perdas visíveis (PVA), perdas invisíveis (PIA), as perdas totais (PTA), perdas visíveis totais (PVT) e perdas totais na colheita (PTC), dimensionamento das leiras, distribuição de palhas e produtividade real. Para a qualidade fisiológica foram utilizados os seguintes testes: germinação em areia e em papel, primeira contagem de germinação, índice de velocidade de emergência, massa seca de plântulas, envelhecimento acelerado, condutividade elétrica, emergência de plântulas em campo e tetrazólio. Para análise estatística no arranquio, foi utilizado o delineamento inteiramente casualizado com duas velocidades de arranquio. No recolhimento foi utilizado o delineamento em blocos casualizados em parcelas sub-divididas. As parcelas foram compostas por duas velocidades de arranquio, e as sub-parcelas por três velocidades de recolhimento Para a qualidade fisiológica os dados foram submetidos ao teste de Shapiro-Wilk e após foram submetidos à análise de variância pelo teste F juntamente com os dados de sanidade, e as médias comparadas por meio do teste de Tukey com nível 5% de significância. As velocidades máximas e mínimas não influenciaram nas perdas quali-quantitativas das sementes de amendoim.
Keywords: Amendoim; Sementes; Arranquio; Recolhimento; Qualidade fisiológica; Sanidade; Groundnut digger; Combine harvesting; Physiological quality; Health